Associations between UASMS2 polymorphism in leptin gene and growth, carcass and meat quality traits of cattle: a meta-analysis. Issue 2 (1st April 2022) - Wang, Liyun; Raza, Sayed Haidar Abbas; Gui, Linsheng; Li, Shijun; Liu, Xuchun; Yang, Xinran; Wang, Sihu; Zan, Linsen; Zhao, Chunping
Abstract: Although numerous studies investigated the effect of UASMS2 polymorphism in leptin gene on cattle production, a consensus has not yet been reached. Therefore, we reviewed and meta-analyzed the effects of UASMS2 on cattle. We searched potentially relevant studies from seven databases (to December 25, 2019). Standard mean difference along with 95% confidence intervals was calculated to assess the strength of association through the random-effects model. Six published articles containing 1378 cattle samples were included in our meta-analysis. We found UASMS2 was not related to carcass weight, dressing percentage and loin muscle area in the recessive genetic model, but there was a significant association between UASMS2 and average daily weight gain, dry matter intake, body weight, marbling score, and backfat thickness. This meta-analysis indicated that UASMS2 was associated with growth and meat quality traits of cattle, implying that this SNP can be used reliably in beef cattle breeding. This study may provide valuable information on improving beef yield and quality in cattle production.